ISOPROPYL N-(3-CHLOROPHENYL) CARBAMATE (CIPC) RESIDUES IN POTATOES TREATED WITH FOG AND DUST FORMULATIONS DURING STORAGE - Singh, Brajesh; Ezekiel, R (Potato Journal, 2013)
Potatoes (cv. Kufri Lauvkar) stored at 10 and 12Â°C were treated with two formulations of CIPC, viz., aerosol and dust and residue levels were determined periodically. Aerosol formulation applied as fog resulted in more even distribution as indicated by higher level of CIPC residue in peels and unpeeled tubers. However, the highest CIPC residue level observed was much below the acceptable limit.